Historical developments in veterinary pharmaceutical industry in türkey - Rahşan Öztürk (Eurasian Journal of Veterinary Sciences)
Drug applications in veterinary medicine were introduced with the domestication of animals. Although drug applications in modem sense started with the establishment of first veterinary school in 1842, no industrial initiative was taken place during Ottoman period. The basis of Veterinary Pharmaceutical Industry was set up in the middle of the 20th century with the introduction of industrial drug production. The aim of this study was to fulfil to need in this aspect and to provide data for future studies. In addition to provision of original document and analysis of historical methodology, a questionnaire survey was applied II has been concluded thai the veterinary pharmacentical industry in Turkey my acquire a similar quality to western models by means of arrangements in Ihe light of EU directives and complementary requirements may be performed repidly.